Unpacking bilingualism in English Language Teaching: An empirical study of Weinreich’s typology in the Indonesian EFL context - Aditya Sahrul Akbar; Hanandyo Dardjito; Nadya Septiani Rahman; Ma. Azalea Candyd B. Redoble (Universitas Sarjanawiyata Tamansiswa, 2025)
The process of acquiring the target language cannot be separated from the aspect of bilingualism, which explains how an individual can acquire a second language. Thus, this research aims to analyze how English teachers acquire English as their target language. The analysis is based on the three types of bilingualism proposed by Weinreich (1953). In addition, this study aims to identify the type of bilingualism that is most commonly used by teachers in the context of English learning. A qualitative research design was employed in this study to investigate the topic qualitatively, utilizing data analysis techniques as outlined by Miles & Huberman (2014). The data in this research were collected through questionnaires, interviews, and video observations of two teachers who actively teach English at a vocational school in Yogyakarta. The results show that in language acquisition, subordinate and coordinate bilingualism emerge as the most dominant types of bilingualism in how teachers acquire their target language. Additionally, subordinate is a type of bilingualism that is often used by both teachers in the ELT context. Future research can explore the correlation between parenting patterns and the process of acquiring an individual's target language.